2017
DOI: 10.1002/eco.1860
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatic and ecohydrological resistance/resilience conditions across tropical biomes of Costa Rica

Abstract: Water resources management in the tropics is challenged by climate variability and unregulated land use change and their impacts on the complex interactions between vegetation, soil, and atmosphere. This study focuses on the analysis of hydroclimatic and ecohydrological conditions across 6 major biomes in Costa Rica. Using the Budyko and the Tomer–Schilling frameworks, 31 reanalysis data points located across the Caribbean and Pacific domains were classified according to their ecohydrological resistance and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
(129 reference statements)
1
19
0
Order By: Relevance
“…These correlation values were similar to those reported over different regions of the Iberian Peninsula, including island environments like Mallorca and several coastal sites [9]. Such relationships also allowed a further adjustment of the data to fit the observations by adopting a spatial bias (error) correction method like the one applied to precipitation data [21,42,43]. As mentioned above, due to the location of Costa Rica on the narrow land-bridge of Central America, the MODIS near-infrared water vapor retrieval algorithm could be greatly affected and the derived column water vapor values over coastal or water areas may vary significantly due to the lower signal-to-noise ratios of the measured spectra [13].…”
Section: Discussionsupporting
confidence: 83%
“…These correlation values were similar to those reported over different regions of the Iberian Peninsula, including island environments like Mallorca and several coastal sites [9]. Such relationships also allowed a further adjustment of the data to fit the observations by adopting a spatial bias (error) correction method like the one applied to precipitation data [21,42,43]. As mentioned above, due to the location of Costa Rica on the narrow land-bridge of Central America, the MODIS near-infrared water vapor retrieval algorithm could be greatly affected and the derived column water vapor values over coastal or water areas may vary significantly due to the lower signal-to-noise ratios of the measured spectra [13].…”
Section: Discussionsupporting
confidence: 83%
“…The region is exposed annually to a marked dry season (December–April), during which water supply is highly contested among the different productive sectors (Kuzdas et al, ), followed by a wet season with high interannual rainfall variability (Steyn et al, ). This typical dry season is frequently intensified by several climatic mechanisms, such as El Niño (Esquivel‐Hernández et al, ; Steyn et al, ), which, as observed during the recent El Niño 2014–2016 event, can result in regional drought and water‐related conflicts (Kuzdas & Wiek, ; Vignola et al, ). Moreover, current climate change projections predict a reduction in precipitation and intensification of drought in the region (Hidalgo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the tropical belt is mostly covered with oceans, precipitation is not easy to monitor. Tropical ecohydrological conditions are usually under the influence of complex land–ocean–atmosphere interactions (Esquivel‐Hernández, Sánchez‐Murillo, Birkel, Good, & Boll, ; Wilcox & Asbjornsen, ) that produce a dynamic cycling of mass and energy composed of water vapour mixing ratio distributions, cloud formation mechanisms, precipitation and convergence, ecohydrological connectivity and services, groundwater recharge processes in complex aquifers, runoff generation, rapid land use changes, and vegetation dynamics.…”
Section: Prefacementioning
confidence: 99%
“…However, as the tropical belt is mostly covered with oceans, precipitation is not easy to monitor. Tropical ecohydrological conditions are usually under the influence of complex land-oceanatmosphere interactions (Esquivel-Hernández, Sánchez-Murillo, Birkel, Good, & Boll, 2017;Wilcox & Asbjornsen, 2018) Brooks, Elliot, & Boll, 2015) to tracer-aided modelling (Tunaley, Tetzlaff, Birkel, & Soulsby, 2017). Despite the recent advances in understanding stable isotope dynamics in hydrological studies, ecological assessments, climate variability analysis, and reconstructing paleoclimate conditions, a consensus exists regarding the urgent need for long-term and better spatial coverage of monitoring efforts.…”
Section: Prefacementioning
confidence: 99%